2021
DOI: 10.1002/2050-7038.13044
|View full text |Cite
|
Sign up to set email alerts
|

Frequency control scheme with dynamic droop characteristics of a DFIG for mitigating the frequency fluctuations

Abstract: Summary The variations of wind generation result in the considerable fluctuations of the system frequency, which are difficult to be regulated in the acceptable range in electric power systems with highly penetrated wind generations. This paper suggests an enhanced frequency control scheme with dynamic droop coefficients of a doubly fed induction generator (DFIGs, type 3) that is able to mitigate the fluctuations of the system frequency with more efficiency. To this end, a supplementary control loop with syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This study was concluded that the proposed approach is more successful in improving the maximum rate of frequency change and frequency nadir under varied disturbance sizes, even with fluctuating wind speed. In [137], Yang et al presented an improved frequency control strategy using dynamic droop coefficients of type 3 WECS that effectively mitigates system frequency variations. The results of simulation were indicated that the proposed frequency control method is useful to enhance the capability of frequency regulation under several patterns of wind speed and the penetration levels especially for power systems with highly wind generation.…”
Section: Recent Frequency Control Methodsmentioning
confidence: 99%
“…This study was concluded that the proposed approach is more successful in improving the maximum rate of frequency change and frequency nadir under varied disturbance sizes, even with fluctuating wind speed. In [137], Yang et al presented an improved frequency control strategy using dynamic droop coefficients of type 3 WECS that effectively mitigates system frequency variations. The results of simulation were indicated that the proposed frequency control method is useful to enhance the capability of frequency regulation under several patterns of wind speed and the penetration levels especially for power systems with highly wind generation.…”
Section: Recent Frequency Control Methodsmentioning
confidence: 99%